Rhetorical Moves of Research Article Abstracts in Linguistics and Language Education with Different Quartile Level - Triyanna, Wahyuni; Harahap, Alamsyah; Yunita, Wisma (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2025)
Writing an abstract in a research article is very important. The existence of abstract is compulsory in a research article. It is a research summary that must be attached and presented with the article. This study aims to identify moves and the most common pattern in RA abstracts in linguistic and language journals with different quartiles level. By using descriptive qualitative method, eighty RA abstracts of linguistic and language education journals with different quartile level were extracted from eight journals. The result finding; 1) Move 2 (Aim/Purpose) exists in seventy RA abstracts, Move 3 (Method) is present in sixty two RA abstracts, and Move 4 (Finding/Result) appears in Seventy Eight RA abstracts. In contrast, Move 1 (Introduction) is found in only 50 RA abstracts, and Move 5 (Conclusion) appears in 31 RA abstracts. 2) Q1 journal have the most frequent move, indicating a more comprehensive and detailed structure in their abstracts. In contrast, journals in lower quartiles, such as Q3 and Q4, often feature abstracts with fewer moves. As this study focuses only on the rhetorical move and pattern of RA abstract in field of linguistic and language journal with different quartile level, future research should conduct a comparative study and language features of the RA abstract in the field of across discipline with different quartile level.